Least developed countries (LDCs): newly determined - Udo E. Simonis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
When in 1998 ECOSOC decided to reconstitute the previous Committee for Development Planning under name Committee for Development policy, it mandated the new CDP, among other tasks, to ,,… continue the triennial review of the status of least developed countries“, with the next review to be held in the year 2000. The review has been conducted every three years since 1991, when two composite indices were introduced to replace two single indicators to better reflect the structural weakness of low level of human resources and low degree of economic diversification.
Keywords: 300; Entwicklungsindikator; Index; Vierte Welt